PLEIOTROPIC EFFECTS OF STATINS - Помыткина, Татьяна Евгеньевна; Линсцер, Полина Анатольевна; Драганов, Эдуард Александрович (Medicine in Kuzbass, 2025)
Statins are among the most widely prescribed medications worldwide and are known for their hypolipidemic effects. However, in recent years more and more data have been accumulated regarding the beneficial effects of statins, beyond lowering the cholesterol level alone. The article reviews and analyzes available publications on the pleiotropic effects of statins. The overview of Russian and foreign sources was performed based on the analysis of materials from scientific medical journals and databases such, as CyberLeninka, Pub Med, and Google Scholar. The data obtained this way expands the understanding of the pharmacological properties of statins and opens new perspectives for their clinical use. In particular, the mechanisms of their influence on common chronic diseases such, as atherosclerosis, cancer, and dementia are considered. Possible influences of statins on the course of the inflammatory process in the context of chronic diseases are as follows: rheumatoid arthritis, chronic liver inflammation. In addition in one of the publications, mentioned in this article, there was a study that considered the possibility of higher efficacy of lipophilic statins compared to hydrophilic statins.